Active Ingredients and Anti‐Arthritic Mechanisms of Ba‐Wei‐Long‐Zuan Granule Revealed by 1H‐NMR‐Based Metabolomics Combined with Network Pharmacology Analysis. Issue 6 (13th May 2020) - Fan, Gang; Li, Qi; Li, Hai‐Jiao; Zhang, Yun‐Sen; Xu, Xin‐Mei; Fang, Gang; Ge, Yi‐Man; Du, Lei‐Lei
Abstract: Ba‐Wei‐Long‐Zuan granule (BWLZ) is a traditional herbal preparation. It has been widely used for the treatment of rheumatoid arthritis (RA). However, its active ingredients and mechanisms of action are still unclear. The present study aims to reveal the active compounds and anti‐arthritic mechanisms of BWLZ against collagen‐induced arthritis (CIA) by using 1 H‐NMR‐based metabolomics, molecular docking and network pharmacology methods. After 30 days of administration, BWLZ could effectively improve the metabolic disorders in CIA rats. The anti‐arthritic effect of BWLZ was related to its restoration of 16 disturbed serum metabolites. Molecular docking and network analysis showed that 20 compounds present in BWLZ could act on multiple targets. Among them, coclaurine and hesperidin showed the highest hit rates for target proteins related to both metabolic regulation and RA, indicating that these two compounds might be potential active ingredients of BWLZ. Moreover, pathway enrichment analysis suggested that the anti‐arthritic mechanisms of BWLZ might be attributed to its network regulation of several biological processes, such as steroid hormone biosynthesis, mTOR signaling pathway, alanine, aspartate and glutamate metabolism, and synthesis and degradation of ketone bodies. These results provide further evidence for the anti‐arthritic properties of BWLZ and are beneficial for its quality control and clinical application. The potential targets and biological processes found in this study may provide valuable information for further studying the molecular mechanisms of BWLZ against RA. In addition, our work provides new insights for revealing the active ingredients and regulatory mechanisms of complex herbal preparations. Abstract :